2016
DOI: 10.20463/jenb.2016.06.20.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term whole-body vibration and aerobic exercise on body composition and bone mineral density in obese middle-aged women

Abstract: [Purpose]The purpose of this study was to determine the effectiveness of whole-body passive vibration exercise and its differences from aerobic exercise on body composition, bone mineral density (BMD) and bone mineral content (BMC).[Methods]Obese middle-aged women (n=33 out of 45) with 34±3% body fat completed the training protocol. They were randomly assigned into diet (n=9; control group), diet plus whole-body vibration exercise (n=13; vibration group), and diet plus aerobic exercise (n=11; aerobic group) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In the same line, Nam et al 15 suggested that vibration exercise was as effective as aerobic exercise in reducing fat mass when combined with dietary intervention; however to our knowledge, no previous studies have assessed both interventions combined on body composition. Based on the aforementioned findings, it is possible that HIIT, which has a positive effect on adiposity, 8 may be used in combination with WBV as this modality is also associated with a change in fat mass in addition to improvements in blood flow.…”
Section: Introductionmentioning
confidence: 92%
“…In the same line, Nam et al 15 suggested that vibration exercise was as effective as aerobic exercise in reducing fat mass when combined with dietary intervention; however to our knowledge, no previous studies have assessed both interventions combined on body composition. Based on the aforementioned findings, it is possible that HIIT, which has a positive effect on adiposity, 8 may be used in combination with WBV as this modality is also associated with a change in fat mass in addition to improvements in blood flow.…”
Section: Introductionmentioning
confidence: 92%
“…WBV training has been recognized as an alternative exercise training to improve physical fitness also in obese subjects [10,12,13]. WBV stimulus is applied through a vibration platform which delivers high-frequency mechanical stimuli (Hz) with a small amplitude (mm).…”
Section: Salivary Cortisol Levelsmentioning
confidence: 99%
“…In the last years, whole-body vibration (WBV), which is applied using a vibration platform on which a subject stands performing exercise while receiving a vibratory stimulus, has become a common exercise used as alternative exercise modality to improve physical fitness and physical performance in obese [10] and non-obese [11] subjects. Several studies showed that long-term WBV practice has positive effects on body composition, bone mineral density, and heart rate (HR) variability [12,13]. Moreover, it is well established that a single session of WBV positively influences the anabolic hormones in aged individuals [14], and in obese subjects [15].…”
Section: Introductionmentioning
confidence: 99%
“…Two surveys 40,46 used acute vibration training responses and the rest, training interval ranging from 4 to 12 weeks. [41][42][43][44][45][47][48][49][50][51][52] The first two findings of this review were reports from Vissers et al 40.41 The first aimed to closely examine and compare improvement in oxygen uptake levels (O 2 ) during resistance exercise (RE) sessions by adding IVC. In the second study, now a chronic context, vibratory exercises were associated with aerobic exercises (AE), in an attempt to identify if the results could positively affect body weight (BW), body composition (BC), BMI, heart rate (HR), and factors linked to metabolic syndrome (MS).…”
Section: Discussionmentioning
confidence: 99%